2018
DOI: 10.1002/jmv.25277
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hepatitis C genotypes in Uttar Pradesh, India; rare genotype 4 detected

Abstract: HCV GTs 3a and 1a are the commonest circulating GTs in Uttar Pradesh, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…7 HCV GT-3 is the second most prevalent genotype worldwide, but the prevalence of GT-3 in this study was highest i.e., 83%. Previous data shows that GT-4 was very rare with detection rates of less than 0.5% in the subcontinent 8 , however its prevalence in this study was 3.7%. Perhaps it was under diagnosed previously or maybe it is emerging as a new cause of chronic HCV now.…”
Section: Discussioncontrasting
confidence: 83%
“…7 HCV GT-3 is the second most prevalent genotype worldwide, but the prevalence of GT-3 in this study was highest i.e., 83%. Previous data shows that GT-4 was very rare with detection rates of less than 0.5% in the subcontinent 8 , however its prevalence in this study was 3.7%. Perhaps it was under diagnosed previously or maybe it is emerging as a new cause of chronic HCV now.…”
Section: Discussioncontrasting
confidence: 83%
“…Many studies reported an association between injections drug user (IDU), female sex workers (FSW), men sex with men (MSM) and HCV, and some study reported associated risk patient; β-thalassemia, visceral leishmaniasis, jaundice, dialysis, three studies combined measure 12% prevalence in pregnant women, and also reported slum population and primitive groups with 6% prevalence (Table 2). 1,4,8,[14][15][16][17][18][19]20,22,23…”
Section: Resultsmentioning
confidence: 99%
“…5 A study conducted in Uttar Pradesh by Prakash et al reported that the prevalent genotypes and subtypes of HCV was found to be 25%, 2.9%, 0.25%, 68.07%, 2.2%, 0.49%, 0.74% and 0.24% for the genotypes 1a, GT1b, GT1c, GT3a, GT3b, GT3g, GT3i and GT4a, respectively. 14 Whereas HCV genotypes GT2, GT5 and GT6 were not detected in that population and GT3a and GT1b were the commonest.…”
Section: Hcv Genomementioning
confidence: 86%